EVALUATION OF GRADUAL MASS LOSS OF DIFFERENT NICKEL-TITANIUM INSTRUMENTS AFTER REPEATED USES IN SIMULATED CANALS - Rodrigues, Ana Clara de Souza; Oliveira, Helloísa Christina da Cunha; Silva, Lara Moisés; Camilo, Naira Geovana; Endo, Mônica Misaé; Guedes, Orlando Aguirre; Oliveira, Helder Fernandes de (CIPEEX, 2024)
The aim of this study was to evaluate the gradual mass loss of different nickel-titanium (NiTi) instruments after repeated uses in simulated canals. Four different instrument systems were used: Group 1. Protaper Ultimate®; Group 2. Trunatomy®; Group 3. Wave One Gold® and Group 4. Reciproc Blue®. Each instrument from each group was initially weighed on a high-precision digital analytical scale to obtain the initial weight (IW). Each group performed the instrumentation of five simulated canals using the X-Smart Plus® electric motor, following each manufacturer’s sequence. After this step, a new weighing was performed to obtain the final weight (FW). The gradual mass loss of each instrument was calculated by the difference between the IW and FW of each instrument. After obtaining the results, statistical analysis was performed. After verifying the sample normality, an analysis of variance (P <0.05) was performed. The Tukey test was then used for multiple comparisons between the groups.